2019
DOI: 10.2174/1570161116666180703094919
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 and Arterial Stiffness in Patients with Heart Failure: A Pilot Study

Abstract: Background: Cardiac performance depends on optimum ventriculoarterial coupling which is impaired in patients with heart failure (HF). Galectin-3 is a mediator of myocardial fibrosis and remodeling, and is associated with clinical status in patients with chronic HF. We examined the association of arterial stiffness with galectin-3 levels in patients with HF of ischemic etiology. Methods: We consecutively enrolled 40 patients with stable ischemic HF and reduced ejection fraction. Central aortic stiffness was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Oikonomou et al observed the role of Galectin-3 in myocardial remodeling, fibrosis, and clinical status of HF patients, and the possible association with increased central arterial stiffness and impaired ventriculoarterial coupling. 20 Abbreviation: AUC, area under the curve. Combined ROC curves showed that Galectin-3 has higher AUC compared with NT-proBNP in HFpEF cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oikonomou et al observed the role of Galectin-3 in myocardial remodeling, fibrosis, and clinical status of HF patients, and the possible association with increased central arterial stiffness and impaired ventriculoarterial coupling. 20 Abbreviation: AUC, area under the curve. Combined ROC curves showed that Galectin-3 has higher AUC compared with NT-proBNP in HFpEF cases.…”
Section: Discussionmentioning
confidence: 99%
“…Oikonomou et al observed the role of Galectin-3 in myocardial remodeling, fibrosis, and clinical status of HF patients, and the possible association with increased central arterial stiffness and impaired ventriculoarterial coupling. 20 Thus, Galectin-3 is thought to augment fibrosis and modulate immune response, both are pivotal processes leading to maladaptive cardiac remodeling, 21 which will ultimately lead to LV dysfunction and HF. Various studies showed that Galectin-3 expression is upregulated in patients with decompensated HF.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with rheumatoid arthritis, galectin-3 had a markedly positive association with arterial stiffness and atherosclerosis presented as increased PWV, carotid artery intima-media thickness, systemic vascular resistance, pulse pressure, and decreased total arterial compliance [ 20 ]. In addition, galectin-3 positively correlated with PWV in patients with chronic heart failure and hemodialysis after adjustment for confounders [ 21 , 22 ]. Overall, galectin-3 might have a role in cross-talk between vascular stiffness or remodeling and myocardial remodeling and mediate the process of endothelial dysfunction [ 23 , 24 ]; when both mechanisms occur, CVD develops.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, plasma galectin-3 correlates with a lower or even rapidly declining estimated glomerular filtration rate (eGFR) [ 13 , 19 ]. Furthermore, galectin-3 is independently associated with pulse wave velocity (PWV), carotid intima-media thickness, and systemic vascular resistance [ 20 , 21 , 22 ]. It also mediates the process of endothelial dysfunction [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, galectin-3 is considered not only as a powerful predictive biomarker of incident HF, but also as a mediator of T2DM progression [129,130]. Among HFpEF patients, the levels of galectin-3 were significantly positively associated with age, creatinine clearance, arterial stiffness (determined by the measurement of carotid femoral pulse wave velocity), aldosterone and BNP levels, and inversely correlated with LV ejection fraction [131][132][133]. Among 1386 patients with a ≥1 risk factor for HF (e.g., hypertension, T2DM, and atherosclerotic CVD) or previously suspected HF, that were enrolled in the DIAST-CHF study, galectin-3 levels of >313.57 ng/mL (sensitivity = 0.61 and specificity = 0.73) predicted incident HFpEF, adjusted all-cause mortality, and the adjusted composite of CV hospitalization and death [134].…”
Section: Galectin-3mentioning
confidence: 99%